Cystic fibrosis-related diabetes in the era of modern treatment using CFTR modulators in pediatric patients—a systematic review - Pietrzykowska, Anna; Darmoń, Jerzy; Szymocha, Katarzyna; Donocik, Wiktoria; Tarasiewicz, Mateusz; Stadnik, Julia; Jarosz-Chobot, Przemysława (Frontiers in Pediatrics, 2025)
BackgroundCystic fibrosis-related diabetes (CFRD) is a common comorbidity in cystic fibrosis (CF), particularly in the pediatric population. As cystic fibrosis transmembrane conductance regulator modulators (CFTRm) become widely used, there is growing interest in their potential metabolic benefits. This systematic review evaluates the effects of CFTR modulators on glucose metabolism and glycemic control in children and adolescents with CFRD.Materials and methodsFollowing PRISMA guidelines, we conducted a literature search in PubMed, Scopus, and Medline for all papers until 2025. Eligible studies included clinical trials, observational studies, chart reviews, and case reports focusing on pediatric patients receiving CFTRm.ResultsFrom almost 653 initially identified records 5 studies met inclusion criteria - 1 clinical trial, 2 observational studies and 2 case reports. Evidence suggests CFTRm may improve glucose tolerance and insulin secretion in some pediatric patients, particularly in those with preserved β-cell function or early-stage CFRD. However, results varied across studies with some showing no significant improvements in glycemic control.ConclusionsWhile early findings suggest CFTR modulators may offer metabolic benefits and potentially delay or reduce the need for insulin therapy in children CFRD, current evidence is limited. Larger, pediatric-focused clinical trials with standardized glycemic outcomes are essential to determine the long-term efficacy and safety of CFTRm in managing or preventing CFRD.